Semantic Study of Abstract Nouns on the Example of Uzbek-English Literary Texts (Journal of Pedagogical Inventions and Practices, 2022)
In modern society, tourism plays an important role in the development of the economy. It should be noted that the main factors in attracting English speaking tourists to our country today depend on the decoration of the site created by travel agencies, the correct and accurate presentation of various words, phrases and realia in translation, as well as the linguistic skills of the site. In this article, we have tried to reveal some semantic features of the translation of the most commonly used realia from English into Uzbek on the sites of travel agencies. In this case, we have taken the example of the English-Uzbek-English translation of the realia used on the websites of some travel agencies operating in Uzbekistan.